2021
DOI: 10.15252/embr.202051023
|View full text |Cite|
|
Sign up to set email alerts
|

Overlapping roles for PLK1 and Aurora A during meiotic centrosome biogenesis in mouse spermatocytes

Abstract: The establishment of bipolar spindles during meiotic divisions ensures faithful chromosome segregation to prevent gamete aneuploidy. We analyzed centriole duplication, as well as centrosome maturation and separation during meiosis I and II using mouse spermatocytes. The first round of centriole duplication occurs during early prophase I, and then, centrosomes mature and begin to separate by the end of prophase I to prime formation of bipolar metaphase I spindles. The second round of centriole duplication occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Mice possessing loxP sites flanking exon 3 of the Aurka gene [ 33 ] were obtained from (C57BL/6N; Aurkatm1c(EUCOMM)Hmgu/J) the International Mouse Phenotyping Consortium (IMPC; www.mousephenotype.org ). To generate Aurka fl/fl Gdf9-Cre mice, female mice carrying the Aurka floxed alleles were crossed with Gdf9-Cre males (Jackson Laboratories Tg (Gdf9-icre)5092Coo/J, #011062).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice possessing loxP sites flanking exon 3 of the Aurka gene [ 33 ] were obtained from (C57BL/6N; Aurkatm1c(EUCOMM)Hmgu/J) the International Mouse Phenotyping Consortium (IMPC; www.mousephenotype.org ). To generate Aurka fl/fl Gdf9-Cre mice, female mice carrying the Aurka floxed alleles were crossed with Gdf9-Cre males (Jackson Laboratories Tg (Gdf9-icre)5092Coo/J, #011062).…”
Section: Methodsmentioning
confidence: 99%
“…To test if AURKC can compensate for loss of AURKA, and to further understand the role of AURKA during meiosis in mouse oocytes, we generated a mouse strain that lacks Aurka [ 33 ] specifically in oocytes using Gdf9 -mediated Cre excision [ 34 ]. Consistent with AURKA being the most abundant AURK in oocytes [ 31 ], we demonstrate that AURKA is essential for oocyte maturation through fragmenting aMTOCs, regulating localization of TACC3 at the spindle and may have an unknown function to promote anaphase onset.…”
Section: Introductionmentioning
confidence: 99%
“…AURKA, AURKB and AURKC belong to a family of kinases with high sequence homology (Tang et al, 2017). AURKA participates in centrosomes dynamics in male mouse meiosis (Alfaro et al, 2021;Wellard et al, 2021), while AURKB and AURKC (hereafter denoted collectively as AURKB/C) function as the catalytic subunit of the CPC, presenting overlapping functions in spermatogenesis (Jordan et al 2021).…”
Section: Aurkb/c Phosphorylation Is Reduced At Centromeres When H3t3 Phoshorylation Is Abolishedmentioning
confidence: 99%
“…The gain or loss of chromosomes often originates from dysregulation of centromere assembly, errors in kinetochore-microtubule interaction, or chromosome congression failures. These processes are highly regulated and well-orchestrated by several master regulators, such as PLK1 and Aurora B kinase (AURKB) among others, which perform their role in both mitosis (Lukasiewicz and Lingle, 2009;Nikonova et al, 2013;Schmucker and Sumara, 2014) and meiosis (Alfaro et al, 2021;Wellard et al, 2021). A recently described and poorly studied regulator is the kinase Haspin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AURKs are clearly involved in the regulation of chromosome segregation. However, very little is known about expression or functions of AURKs when it comes to meiosis—some studies have confirmed that, for instance, AURKA together with Polo-like kinase 1 (PLK1) is required for the correct migration of duplicated centrosomes at male meiosis I and II in order to form a bipolar spindle [ 8 , 9 ]. Furthermore, it is unknown why there is the additional isoform AURKC present in germ cells of eutherian mammals, or why it is not present in marsupials.…”
Section: Introductionmentioning
confidence: 99%